The Phantom Menace: Viceroy Pezuela against the Liberating Expedition (1818-1820) - Alvarado Luna, Patricio A. (2021)
After the battle of Maipu in 1818, the next step in San Martín’s plan to ensure independence was to head to Peru. For this, a plan was formed that took almost two years to complete: The Liberating Expedition. During this time, from the Peruvian viceroyalty, Viceroy Pezuela, fearful of his arrival, made various defensive measures for Lima and the viceregal coast. This fear generated a collective fear and various questions to the viceroy. This article analyzes, focusing in the Memoria of Pezuela, the viceregal situation from the first rumors of the formation of the Liberating Expedition in 1818 until its arrival in 1820.